Development Of Technology And Science In Islamic Religious Education - Pebriana, Dila Rahma; Khoirunissa, Dhea; Supriadi, Ananda Bagus (Noor: Journal of Islamic Studies, 2025)
The development of technology and science has brought about significant transformations in religious education, especially Islamic Religious Education. Technology plays a role as an effective means to introduce and deliver religious material in a modern and interesting way, especially for the millennial generation who have a high tendency towards the use of digital and audio-visual media. The use of audio-visual-based technology such as learning videos, as well as internet technology such as e-learning and email, facilitates the process of distance and interactive learning, thereby increasing students' understanding of religious material. [1} In addition, digital technology opens up wide opportunities in the accessibility of Islamic educational resources globally, allowing individuals from various regions to access Islamic literature and interact directly with educators and fellow students through online platforms and social media. This enriches the experience of religious learning with methods that are more creative, interactive, and in accordance with the times. However, challenges such as the authenticity of content and the gap in access to technology also need to be anticipated so that the benefits of technology can be optimal. The development of technology in religious education also encourages the renewal of teaching methods and the improvement of teacher and student skills in using technology effectively. A constructive and participatory learning approach is expected to shape students' motivation to practice religious teachings in everyday life. Thus, the integration of technology and science in religious education contributes to the achievement of educational goals that are relevant to the needs of the digital era and globalization